2023
DOI: 10.3390/su15054221
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Indoor Air Quality in a University Professor’s Office

Abstract: Indoor air conditioning is currently a topic of much interest, not only to save energy but also due to public health issues such as pandemics. This study focuses on the thermal comfort and air quality of a closed, air-conditioned space located in an extremely hot climate. Due to noise and weather conditions, the door and window of the space are kept closed at all times. The study uses computational fluid dynamics techniques and the finite element method. Average temperatures and CO2 concentrations, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Existing research can predict the cooling load and change the operating frequency of air conditioners using the human flow and temperature prediction models [22]. Through the experiment of 1~5 people's airtight measurement, it is found that the indoor air quality of office buildings becomes worse with the different number of people [23].…”
Section: Experimental Theoretical Basismentioning
confidence: 99%
“…Existing research can predict the cooling load and change the operating frequency of air conditioners using the human flow and temperature prediction models [22]. Through the experiment of 1~5 people's airtight measurement, it is found that the indoor air quality of office buildings becomes worse with the different number of people [23].…”
Section: Experimental Theoretical Basismentioning
confidence: 99%